2015
DOI: 10.1007/s11356-015-4541-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and source apportionment of particle number concentration at a semi-urban tropical environment

Abstract: Principal component analysis (PCA) and correlation have been used to study the variability of particle mass and particle number concentrations (PNC) in a tropical semi-urban environment. PNC and mass concentration (diameter in the range of 0.25->32.0 μm) have been measured from 1 February to 26 February 2013 using an in situ Grimm aerosol sampler. We found that the 24-h average total suspended particulates (TSP), particulate matter ≤10 μm (PM10), particulate matter ≤2.5 μm (PM2.5) and particulate matter ≤1 μm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 49 publications
1
13
1
Order By: Relevance
“…In this study, we used a value of 0.4 for C, which, according to Ogulei et al (2006b), produced the best Q value as it is the closest to theoretical value and physically interpretable results. Other main researchers have also applied this procedure for the calculation of uncertainty (Harrison et al, 2011;Hedberg et al, 2005;Khan et al, 2015b). An additional 5 % uncertainty was added to cover any methodological errors during the preparation of filter papers, gravimetric mass measurements, and preparing the calibration curves.…”
Section: Mass Closure Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we used a value of 0.4 for C, which, according to Ogulei et al (2006b), produced the best Q value as it is the closest to theoretical value and physically interpretable results. Other main researchers have also applied this procedure for the calculation of uncertainty (Harrison et al, 2011;Hedberg et al, 2005;Khan et al, 2015b). An additional 5 % uncertainty was added to cover any methodological errors during the preparation of filter papers, gravimetric mass measurements, and preparing the calibration curves.…”
Section: Mass Closure Modelmentioning
confidence: 99%
“…Widely used multivariate methods are (a) a chemical mass balance model (CMB) (Watson et al, 1990), (b) positive matrix factorization (PMF) (Paatero, 1997;Paatero and Tapper, 1994), (c) Unmix (Henry, 1987), (d) principal component analysis coupled with absolute principal component score (PCA-APCS) (Thurston and Spengler, 1985), (e) pragmatic mass closure (PMC) (Harrison et al, 2003), and (f) a new source-type identification method for PM 2.5 known as Reduction and Species Clustering Using Episodes (ReSCUE) (Vedantham et al, 2014). PMF is the most reliable method for source-type identification for the following reasons: (i) it uses a weighted least-squares fit and estimates error of the measured data and can impose non-negativity constraints weighing each data point individually (Paatero, 1997;Paatero and Tapper, 1994), (ii) a priori knowledge of pollutants is not necessary, and (iii) it is able to deal with missing values, noisy data, outliers, and values below detection limit (Baumann et al, 2008;Khan et al, 2012Khan et al, , 2015bPolissar et al, 1998a, b). A recent study by Gibson et al (2015) suggested that PMF can resolve PM 2.5 concentrations even below 2 µg m −3 more accurately compared to PMC and CMB.…”
Section: Introductionmentioning
confidence: 99%
“…The number of the particles with the diameter greater than 1 m is very few. As reported by Khan et al [16], more than 90% particle number concentration is dominated by fine particles.…”
Section: Particle Number Concentrationmentioning
confidence: 51%
“…During the southwest monsoon, which is usually associated with the dry season, a high density of biomass fire or wildfires hotspots were reported in the upwind of the sampling location [ Khan et al ., , , , ; Sahani et al ., ]. The dominant boundary‐transported air was from the South Sumatra region.…”
Section: Resultsmentioning
confidence: 99%